Sunflower seed oil for skin barrier repair in newborns: a systematic review and meta-analysis with biophysical parameters - Pratami, R. Rizcky Erika; Budiastuti, Asih; Riyanto, Puguh; Malik, Diah Adriani; Widayati, Retno Indar; Muslimin; Hardian (Journal of Pakistan Association of Dermatologists, 2022)
Background: The skin barrier in newborns is immature, and moisturizers may help repair the barrier. The recommended skincare products for newborns are those containing fewer ingredients. Hence, natural oil-like sunflower seed oil (SSO), free of chemical ingredients, is a cost-effective option. The aim of this study was thus to assess the efficacy of topical SSO to improve skin barriers in newborns. Methods: Online searching in Pubmed-MEDLINE, Scopus, EBSCO, Cambridge Core, ProQuest, Cochrane library, ClinicalTrials.gov, and Google Scholar databases found five relevant articles included in a systematic review (n = 1,272 subjects), from which three articles are used in meta-analysis (n = 908 subject). Results: A meta-analysis showed that following a topical application of SSO, transepidermal water loss (TEWL) tended to lower than other moisturizers (standardized mean difference [SMD] −0.11, confidence interval [CI] 95%, −0.23 to 0.11, p = 0.07, I2 = 0%), and it was not comparable to no moisturizer (SMD 0.09, CI 95%, −0.19 to 0.38, p = 0.52, I2 = 0%). The stratum corneum hydration (SCH) was comparable to other moisturizers (SMD 0.03, CI 95%, −0.20 to 0.26, p = 0.81, I2 = 0%), but it was significantly higher than no moisturizer (SMD 0.77, CI 95%, 0.48 to 1.06, p < 0.00001, I2 = 0%). Qualitative analysis showed that SSO may reduce neonatal skin condition score. Conclusions: A meta-analysis showed that topical application of SSO may act as a moisturizer and improve skin hydration, but it may not repair the barrier. SCH indicates that it increased significantly, which means the hydration improved. The TEWL analysis did not show supportive results for SSO compared to either other moisturizers or control; however, the qualitative analysis did show that SSO had a positive effect on the clinical condition. Keywords: sunflower seed oil, skin barrier, newborn